The relationship between d‐beta‐hydroxybutyrate blood concentrations and seizure control in children treated with the ketogenic diet for medically intractable epilepsy. Issue 3 (19th May 2017) - Buchhalter, Jeffrey R.; D'Alfonso, Sabrina; Connolly, Mary; Fung, Ernest; Michoulas, Aspasia; Sinasac, David; Singer, Rachel; Smith, Jacklyn; Singh, Narender; Rho, Jong M.
Summary: Objective: The ketogenic diet (KD) is a proven treatment for drug‐resistant (DR) seizures in children and adolescents. However, the relationship between seizure control and the most commonly measured metabolite of the diet, the ketone bodyd ‐beta‐hydroxybutyrate (D‐BHB), is controversial. This study was performed to clarify the relationship because specific ketone bodies may be useful as biomarkers of diet efficacy. Methods: Families of children with DR seizures were approached for participation in this open‐label, prospective study when they were referred for the KD at two western Canadian children's hospitals. Inclusion criteria included documentation of DR seizures without exclusion based on age, sex, seizure, or syndrome type. Patients were excluded if they were referred for treatment of a metabolic disorder independent of seizures. Seizures were quantified via parental report and standardized as seizure frequency per 28 days. Epilepsy syndromes were identified on the basis of the medical record. Blood D‐BHB was determined by tandem mass spectrometry. Results: A total of 23 patients were recruited from both sites. Data from five individuals were excluded because these seizures occurred in clusters, leaving 18 patients for the primary analysis. In the latter group, a clear positive correlation was present between measures of seizure frequency and D‐BHB concentrations. However, this failed to reach statistical significance, likely because of the relatively small numbers. Significance: A trend clearly exists between seizure frequency and D‐BHB levels, so we should not be dissuaded by the lack of statistical significance because it possibly results from methodological techniques, especially sample size. These results call for a larger prospective study in which seizure frequency is assessed at the point of care in a standardized fashion so as to determine whether D‐BHB can be used as a reliable biomarker of KD efficacy.